a, f(x)+g(x)= (\(x^5-3\) + 7\(x^4-9x^3+x^2-\dfrac{1}{4}x\))+(\(5x^4-x^5\)+\(x^2\)\(-2x^3+3x^2-\dfrac{1}{4})\)
= \(12x^4-12x^3+5x^2-\dfrac{1}{4}x-\dfrac{13}{4}\)
b, f(x)\(-\)g(x)= (\(x^5-3\) + 7\(x^4-9x^3+x^2-\dfrac{1}{4}x\))\(-\)(\(5x^4-x^5\)+\(x^2\)\(-2x^3+3x^2-\dfrac{1}{4})\)
= f(x)+g(x)= \(x^5-3\) + 7\(x^4-9x^3+x^2-\dfrac{1}{4}x\)\(-\)\(5x^4+x^5\)\(-\)\(x^2\)\(+2x^3-3x^2+\dfrac{1}{4}\)
=2x\(^5\)+2x\(^4\)\(-7x^3\)\(-2x^2\)\(-\dfrac{1}{4}x\) \(-\) \(\dfrac{11}{4}\)
c,Ta có:h(x)+f(x)=f(x) \(\Rightarrow\)h(x)=f(x)\(-\)f(x)=0